Goffin's Cockatoos (Cacatua goffiniana) Can Solve a Novel Problem After Conflicting Past Experiences - Bobrowicz, Katarzyna; O'Hara, Mark; Carminito, Chelsea; Auersperg, Alice M. I.; Osvath, Mathias (Frontiers in Psychology, 2021)
Novel problems often partially overlap with familiar ones. Some features match the qualities of previous situations stored in long-term memory and therefore trigger their retrieval. Using relevant, while inhibiting irrelevant, memories to solve novel problems is a hallmark of behavioural flexibility in humans and has recently been demonstrated in great apes. This capacity has been proposed to promote technical innovativeness and thus warrants investigations of such a mechanism in other innovative species. Here, we show that proficient tool – users among Goffin’s cockatoos – an innovative tool – using species – could use a relevant previous experience to solve a novel, partially overlapping problem, even despite a conflicting, potentially misleading, experience. This suggests that selecting relevant experiences over irrelevant experiences guides problem solving at least in some Goffin’s cockatoos. Our result supports the hypothesis that flexible memory functions may promote technical innovations.